DETERMINATION OF PROGNOSTIC INDICATORS OF TECHNICAL READINESS OF ATHLETES IN COMPETITIVE EXERCISES WITH A FLIGHT PHASE BASED ON VIDEO FOOTAGE - Zagrevsky V.I.; Zagrevsky O.I.; Lavshuk D.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop computational models and a computer application of prognostic indicators of the technical readiness of athletes in competitive exercises with a flight phase based on video footage. Methods and structure of the study. During the experiment, video shooting of exercises, calculation models for the analysis of the technique of sports exercises were carried out. The study group of exercises included acrobatic exercises with a flight phase. Results and conclusions. The original method of constructing a computational model of the flight part of competitive exercises is based on adequate physical and mechanical laws of motion and allows you to form an array of equations for the calculated biomechanical characteristics of an exercise, regardless of the availability of specialized information for calculating the kinematics and dynamics of the flight period. The developed computational model of biomechanical indicators of movement and a computer application can be used for operational control of the level of technical readiness not only of an acrobat, but also of athletes specializing in those sports in which competitive exercises have a flight period.